Practice Briefing A note on auditing fair value of investment properties. Issue 1 (25th February 2021) - Nordlund, Bo; Lorentzon, Johan; Lind, Hans
Abstract : Purpose: The purpose of this article is to study how fair values in financial reports are audited. Design/methodology/approach: The study is a qualitative case study based on in-depth interviews. Findings: One important finding is that auditors anchor in the figure presented by the company, and despite the auditing efforts, there is a substantial risk of management bias in the fair values reported. There is a risk for confirmation bias. Research limitations/implications: Relatively, few respondents were employed in this study, but their background and competence lead to the assessment that the study provides a representative picture of what is being investigated. Practical implications: Auditors may need to develop ways of performing auditing of fair values to reduce the risks identified in this study. Social implications: This study presents a perspective of the auditing process enabling an evaluation of the quality of fair value estimates regarding investment properties in the financial reports. This study also provides users of financial reports as investors, bankers and other institutions with an enhanced understanding of reported estimates of fair (market) values. Originality/value: Very few studies have investigated how auditors evaluate fair values of investment properties. This study contributes by giving users of financial reports an enhanced understanding of the quality of reported estimates of fair (market) values.